Impact of psychosocial stress COVID-19 on job satisfaction: Job stress and job insecurity as mediation variables - Sari, Juwita; Laily, Nur; Pradhani, Fastha Aulia (Fakultas Ekonomika dan Bisnis Universitas Kristen Satya Wacana, 2023)
During a pandemic, the environment around employees is considered a virus carrier, which can endanger their lives. Employees also fear that they will carry the virus and infect their surroundings. This condition is called psychosocial stress. This study aims to prove empirically how psychosocial stress from the impact of COVID-19 can affect employee job satisfaction. Add the variables of job stress and job insecurity as the variables tested indirectly. This study uses a quantitative method with data from the snowball sampling technique on direct sales employees in Surabaya. Two hundred thirty seven samples are obtained. The findings show no direct effect between the psychosocial stress impact of COVID-19 on employee job satisfaction. However, adding indirect test variables, namely job insecurity and job stress, shows significant results. That is, explains that the characteristics of employees in Surabaya agree that they feel the effects of psychosocial stress due to COVID-19. However, these conditions do not affect whether they are satisfied or not at work. Nevertheless, when they feel insecure about their job, and there is stress from work, they feel unsatisfied. The findings of this research provide a theoretical contribution to managing employee stress management in the current turbulent times.